An introduction to Japanese society - Sugimoto, Yshio (Cambridge University Press, 2003)
This book is valuable to both students and teachers. ' Asian Studies Review 'It is refreshing to have an introductory text focus on the constant tension between the diversity of subcultures and the attempts of the center to control them.